Strategic Development Business Plan for the Tourism Company in Prague - Babarykin, Ivan (2017)
In a constantly growing tourism market competition is highly intense, and it can be extremely challenging for a small business to survive, let alone to succeed in this industry. Thus, the development of a strategic plan has a great significance for starting or improving your business. Formulating the main objectives of the company, strategic planning contributes to the creation of a common goal and effective organizational management structures. This academic work is based on the example of a small tourism company in Prague, andthe main goal of the conducted research was to find a practical application in the work of the company, as well as to create a set of actions and solutions aimed at developing a strategy that would contribute to its effective development both in the present and in the future. By analysing company’s internal and external environment and conducting a major survey on decision-making behaviour among the tourists, a number of aspects has been developed such as: 1- mission, vision and goals of the company; 2 – business solutions and recommendations. The outcome of the survey and its analysis will be provided.